The Comparison Effect of DOCA and L-NAME on T Cells Activation in the Preeclampsia Mice Model - Khodijah, Riska Amalia; Christina, Yuyun Ika; Dwijayanti, Dinia Rizqi; Rahayu, Sri; Rifa'i, Muhaimin; Djati, Muhammad Sasmito (Graduate School, Universitas Brawijaya, 2024)
Preeclampsia is a systemic disorder of pregnancy characterized by the maternal immune system's failure to properly adapt to fetal antigens, resulting in chronic inflammatory responses. This research aimed to examine the effects of DOCA (deoxycorticosterone acetate) and L-NAME (Nω-nitro-L-arginine methyl ester) in inducing preeclampsia in pregnant BALB/c mice, focusing on lymphocyte activation. Twenty-four BALB/c mice were randomly divided into four groups: NP (non-pregnant mice), P (healthy pregnant mice), D (pregnant mice received DOCA), and L (pregnant mice received L-NAME). DOCA was dissolved in corn oil and administered subcutaneously at 12.5 mg.kg-1 BW before pregnancy and 6.5 mg.kg-1 BW weekly during pregnancy. L-NAME was administered daily starting from day 5 of pregnancy. Mice were dissected on day 16 of pregnancy, and the spleen was isolated to analyze the relative number of CD4+CD62L+ and CD8+CD62L+ T cells. The results showed that DOCA and LNAME exhibited fewer CD4+CD62L+ and CD8+CD62L+ T cells than healthy pregnant mice. The administration of DOCA at 12.5 mg.kg-1 BW (before mating) and 6.5 mg.kg-1 (day 7 of pregnancy) was more effective in triggering the activation of CD4+CD62L+ and CD8+CD62L+ T cells than the others indicated by the lowest number of CD4+CD62L+ and CD8+CD62L+ T cells. However, the conclusion of which one is more effective in inducing preeclampsia has not been reached. This is due to the many parameters that must be observed related to preeclampsia. Further studies are needed, especially examining proinflammatory cytokine production in T cells after induction with both inducers. Keywords: DOCA, L-NAME, Lymphocyte, Mice, Preeclampsia.